SISTEM INFORMASI MANAJEMEN INVENTARIS BANTUAN BARANG MILIK NEGARA (Studi Kasus : UPT Perpustakaan Universitas Cenderawasih) - Duta Lazarus; Emy L Tatuhey; Jim Lahallo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The Library Technical Unit (UPT) of Cenderawasih University is one of the Technical Implementation Units at Cenderawasih University, providing information technology and communication-based services to support the implementation of the Three Pillars of Higher Education. Currently, the UPT Library of Cenderawasih University uses a manual inventory process and Microsoft Excel to manage Non-Movable Goods (BMN) assistance, which complicates supervision, control, and reporting processes, leading to inaccuracies and delays. Therefore, a web-based BMN inventory management information system is needed to facilitate the inventory data collection and automate the reporting process. With this web-based system, the staff of UPT Library can easily record BMN assistance, track the placement of BMN items in each room, view the status of BMN items, generate comprehensive reports displaying the status of BMN items, and create reports for BMN items placed in each room. The research for this system is conducted using the Waterfall method, system design using UML, and testing using Blackbox Testing. The result of this research is a web-based BMN inventory management information system built using PHP programming language and MySQL database.